2014
DOI: 10.4238/2014.july.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for prehypertension and its cardiovascular risk factors in Inner Mongolia

Abstract: ABSTRACT. Blood pressure levels were evaluated among prehypertension patients with associated cardiovascular risk factors to determine the effect of different interventions with respect to new endpoint events. A total of 1112 patients were equally and randomly divided into control, lifestyle, drug, and lifestyle + drug groups, and were followed-up for 12 months. We collected the age, height, weight, blood pressure, heart rate, blood lipid levels, blood glucose levels, and other clinical data from all subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…No eligible study was found in low-income countries. By continent, the vast majority of studies (84%) were performed in Asia (15 in India, 25 , 27 , 28 , 29 , 32 , 33 , 35 , 36 , 41 , 42 , 44 , 46 , 47 , 48 , 50 12 in China, 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 63 , 66 , 67 , 68 five in Iran, 31 , 37 , 40 , 43 , 45 two in Thailand, 51 , 65 Vietnam, 30 , 49 Bangladesh, 24 , 32 and Sri Lanka, 26 , 32 and one in Jordan, 69 Pakistan, 39 and Mongolia 38 ), followed (14%) by America (three in Brasil, 52 , 64 , 70 two in Colombia, 23 , 62 and one in Cuba 59 ), and only one study (2%) in Africa (Egypt 34 ). To define at-risk populations, most studies selected participants with impaired glucose/prediabetes (52%) or presenting a combination of cardiometabolic risks (34%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation